Eco-Jurisprudence on Deforestation-Induced Disasters: Establishing a Legal Nexus Between Forest Clearance and Environmental Crimes - Emirza Henderlan Harahap (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The escalating frequency of deforestation-induced disasters in the Anthropocene has exposed a significant gap in global ecological governance, where scientific causality often fails to translate into judicial liability. This research explores the integration of eco-jurisprudence and forensic ecology to establish a robust legal nexus between forest clearance and environmental crimes. Using a normative juridical methodology supported by a comparative legal approach, the study analyzes how hydrological modeling and spatial data can be transformed into admissible legal evidence. The results demonstrate that by utilizing the